The Metaphysics of terror : the incoherent system of contemporary politics - Ugilt, Rasmus (Political theory and contemporary philosophy., 2012)
This groundbreaking study aims to provide a philosophical analysis of the phenomenon of terror, in particular the political reactions to it, such as public anxiety and pre-emptive wars, and to re-articulate the understanding of metaphysics through a consideration of its political implications. The book reveals that the key feature of terror is ""potentiality, "" that is, terror is always about ""what could happen"" as opposed to ""what is likely to happen."" This notion helps broaden the scope of the investigation, as the argument spans the ontology, political psychology, political cosmology, a